1999
DOI: 10.1159/000010060
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bacterial Flora of Women with Urethral Syndrome and Interstitial Cystitis

Abstract: The aerobic and anaerobic bacterial flora in the first voided and in the midstream urine of healthy females (n = 5) and female patients with either urethral syndrome (US) (n = 5) or interstitial cystitis (IC) (n = 14) were studied. Bacteria were grown on media enabling isolation of fastidious and aerobic as well as obligatory anaerobic species. In healthy females only gram-positive rods were found whereas US patients also harbored streptococci. Patients with IC presented also with Enterobacteriae and anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Haarala et al . (1999) [9] using culture techniques concluded that bacterial flora of midstream urine from patients with IC clearly differs from that of healthy women, in line with our findings. A study by Zhang et al .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Haarala et al . (1999) [9] using culture techniques concluded that bacterial flora of midstream urine from patients with IC clearly differs from that of healthy women, in line with our findings. A study by Zhang et al .…”
Section: Discussionsupporting
confidence: 90%
“…Lactobacillus has not only been indicated or shown in IC urine samples from females (100% of the cases in this study and as shown by others [6,9,39]) but also demonstrated in IC urine from a male subject [41]. In our study we also detected a significant increase in abundance of this genus, considering its supposedly commensal presence in human urine from healthy subjects [16,18,19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several studies show a weak correlation between the chronic urinary symptoms, i.e. LUTS and infections with Ureaplasma urealyticum, Mycoplasma hominis and anaerobic bacteria [4][5][6][7]. Although doxycycline treatment has been shown to be eVective in about 70% of women presenting with chronic urinary symptoms, a speciWc infectious organism could be identiWed in only 15% of the cases [7].…”
Section: Introductionmentioning
confidence: 99%